Cinema brasileiro e multiletramentos: ressignificando o ensino-aprendizagem de leitura e escrita nas aulas de língua portuguesa - Vieira, Camila da Costa (2019)
The lack of stimulation and difficulty in writing formal texts in the school environment by the students is a problem often pointed out by teachers. However it is remarkable that the contemporary world is permeated with discursive possibilities to meet the needs of interactions required in the various social spheres, be they local or global. In spite of so many tools that facilitate the interlocution, as the Information and Communication Technologies - ICTs, these in turn, are still not very accessible in the school environment of public education, being necessary to democratize the access to the digital means as a way to enhance the teaching -learning in the various areas of knowledge. For this reason, this dissertation, Brazilian cinema and Multiliteracies: Resignifying teaching-learning of reading and writing in Portuguese language classes sought to respond to the following disquiet: How can the insertion of Brazilian cinema and multiliteracies in school teaching-learning of reading and writing in Portuguese language classes? Therefore, aimed at providing students in a 9th grade class with the development of reading and writing skills in a critical and enjoyable way, through an intervention subsidized by a didactic sequence elaborated by the class teacher based on the model proposed by Dolz, Noverraz and Schneuwly (2004), presented as "Cineleituração - Cinema, reading and production", this one in turn proposed moments with activities directed to the Reading of Films and production of texts of the genre critical review of film. For this counted with a theoretical anchorage based on the authors' studies Claúdio Novaes (2016), Charles Bazerman (2006), José Manuel Moran (2004), Jean-Claude Bernardet (2009), Roxane Rojo (2012), Angela Kleiman (2005), Joaquim Dolz (2004) among others that made possible the paths that have been traveled. It is worth noting that the methodology chosen for this work and the research-action type of a qualitative nature are based on TRIPP (2005) and Picheth, Cassandre, Thiollent (2016). This action research was developed at the Maria José de Lima Silveira State School, located in the city of Sobradinho-BA. The results of this work show that the insertion of cinema in Portuguese Language classes can promote a teaching-learning in order to involve and stimulate the students to the numerous practices of reading and writing and thus allow them to develop activities that involve multiliteracies, reading and writing. So much so that from what was worked, the students constructed learning about what was proposed and felt motivated to develop not only what had been planned, but they became protagonists in this process, producing works that demonstrate that besides having built knowledge could be protagonists of the process of teaching and learning.